The Embedded Experience of Racialised Space. The Case of the Descendants of Algerians in Marseille Through the Sayad’s Gaze - Ragone, Marianna (Italian Sociological Review, 2025)
In this contribution, we will attempt, in line with the legacy left to us by Abdelmalek Sayad, to start from spatial conditions in order to analyse more broadly the national/not national representations made by the descendants of Algerians, born and raised in France. The investigation will be based on ethnographic research carried out in the Belsunce neighbourhood in Marseille, which began in September 2022 and ended in September 2023. The questions the research aims to answer are: what is the representation of spaces made by young descendants of Algerians? How does the neighbourhood participate in the production and reproduction of the national/non-national categorisation (Sayad, 1979) that affects the descendants of migrants? The article therefore questions the description of Belsunce made by some young descendants of Algerians women and men who live there or work there. Through their words, their reflections and the observation of the spatial practices they implement, it is possible to notice how Belsunce, and therefore Marseille as a whole, is the product of the persistent effects of the colonial organisation of space and also how the neighbourhood participates in the reproduction of processes of colonial categorisation and racialisation; French/non-French, national/non-national, civilised/uncivilised, integrated/barbarians. Confirming that space is not only structured but also structuring.